E-Waste-An Emerging Public Health Threat: Bangladesh Perspective (Journal of Preventive and Social Medicine, 2023)
Electronic waste or e-waste is emerging as a major public health threat worldwide including Bangladesh because of rapid advances in technology leading to the generation of large amount of wastes and a lack of knowledge in handling of these wastes. The present review discusses the existing e-waste problem in Bangladesh, as a public health concern, and necessary recommendations to have effective e-waste management. This is a traditional review study. The burden of e-waste, regulations and its impact on health at the global and country level were identified using various search engines such as PubMed, Google Scholar, Scopus and ScienceDirect. Books, case studies, legislation documents, reports, original articles and other documents from international organizations and specific governmental agency websites were retrieved. Out of more than 100 research articles on e-waste and health impact in total, 45 original articles, reports, case studies and documents were used for this review. About 400,000 tonnes of electronic waste have been generated across the country in 2018 and that the amount grows by 20% every year. The generation of e-waste rate in Bangladesh has surpassed 72 million tons, which is a 33% increase over the previous decade. According to a study report by Bangladesh University of Engineering and Technology (BUET), e-waste volumes in Bangladesh will rise to 4,62 million tonnes by 2035. Harmful contents of e-waste mainly include lead, cadmium, mercury, chromium, copper, nickel, lithium, Beryllium long term exposure of which may cause health effects like damage to brain, kidney, liver, nervous systems, blood systems, endocrine system, reproductive system and produce stomach cramps, allergic dermatitis, asthma, bronchitis and also develop life threatening disease like cancer. The current review shows that the e-waste poses a serious public health threat leading to significant environmental and health risks. Most of the developing countries including Bangladesh were found to be lagging behind in the implementation of environmentally sound formal recycling processes. Hence, a better life cycle assessment model which have been successfully implemented in other developing countries should be introduced in Bangladesh.JOPSOM 2021; 41(1):41-48